2016
DOI: 10.3917/sm.091.0077
|View full text |Cite
|
Sign up to set email alerts
|

Influence of minimalist footwear on knee and ankle loads during the squash lunge

Abstract: Squash is associated with a high incidence of knee and ankle joint injuries. The aim of this work was to examine the effects of squash specific, running shoes and minimalist footwear on knee and ankle loads during the lunge movement in squash players. Twelve male squash players performed lunge movements whilst wearing squash specific, running shoes and minimalist footwear. The loads experienced by the knee and ankle joints were calculated. Patellofemoral forces were significantly greater in running shoes (5.10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The results showed that there were no differences in impact forces but that the high-cut footwear had a higher inversion angle at footstrike. Currently there is a trend in court based sports including squash 12 , netball 13 and basketball 14 for players to select minimalist footwear in lieu of traditional sport specific shoes, although the clinical efficacy of minimalist footwear is not yet established for court specific motions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that there were no differences in impact forces but that the high-cut footwear had a higher inversion angle at footstrike. Currently there is a trend in court based sports including squash 12 , netball 13 and basketball 14 for players to select minimalist footwear in lieu of traditional sport specific shoes, although the clinical efficacy of minimalist footwear is not yet established for court specific motions.…”
Section: Introductionmentioning
confidence: 99%
“…Sinclair et al, 12 explored knee and ankle loads during the squash lunge when wearing squash specific and minimalist footwear. Their results showed that peak Achilles tendon force was significantly larger in the minimalist footwear.…”
Section: Introductionmentioning
confidence: 99%